2009
DOI: 10.3844/ajptsp.2009.98.106
|View full text |Cite
|
Sign up to set email alerts
|

The Health Risk of Formaldehyde to Human Beings

Abstract: Problem statement: Formaldehyde was classified as a potential human carcinogen, identified by the US Environmental Protection Agency and International Agency for Research on Cancer as a Class 2A carcinogen. It also can cause irritation to human. However, formaldehyde present in biological fluids or tissues and environment as a result of natural processes or from man-made sources and can be emitted slowly into the air. Formaldehyde was used in many industries, hospitals and research as a sterilizing and preserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 52 publications
0
34
0
Order By: Relevance
“…Among aldehydes, adverse health effects of formaldehyde are well known. Exposure to this compound may increase the risk to develop a myeloid leukemia [38]. Levels of formaldehyde found in the six sampling sites were lower than the short-term guideline value of 100 µg/m 3 (30-minutes average concentration), and the long-term guideline value of 200 µg/m 3 established by WHO [30].…”
Section: Discussionmentioning
confidence: 82%
“…Among aldehydes, adverse health effects of formaldehyde are well known. Exposure to this compound may increase the risk to develop a myeloid leukemia [38]. Levels of formaldehyde found in the six sampling sites were lower than the short-term guideline value of 100 µg/m 3 (30-minutes average concentration), and the long-term guideline value of 200 µg/m 3 established by WHO [30].…”
Section: Discussionmentioning
confidence: 82%
“…The content of formaldehyde can depend upon fish species and storage conditions (Chanarat and Benjakul, 2013). Formaldehyde content noticed in the control samples can be attributed to the conversion of trimethylamineoxide (TMAO) to formaldehyde and dimethylamine (DMA) and its formation is determined by the duration and temperature of storage (Norliana et al, 2009). Leelapongwattana et al (2005) reported on the conversion of trimethylamine-N-oxide demethylase (TMAOase) to dimethylamine (DMA) and formaldehyde during ice storage.…”
Section: Residual Level Of Formaldehydementioning
confidence: 99%
“…Sufficient evidence showed that formaldehyde causes nasopharyngeal cancer, sinonasal cancer, and leukemia in human. However, formaldehyde is not considered to be a reproductive or developmental toxicant (Abdollahi & Hosseini, 2014;Aminah et al, 2013;EFSA, 2014;Tang, Bai, Duong, Smith, & Zhang, 2009;IARC, 2012;Norliana, Abdulamir, Bakar, & Salleh, 2009).…”
Section: Introductionmentioning
confidence: 99%